Unveiling the emotional dynamics of sports : antecedents and consequences of affective expressive behaviors - Fritsch, J. (Journal of Applied Sport and Exercise Psychology, 2024)
Abstract: The variety of visible behaviors after winning or losing in sports reveals a lot about the psychological challenges players face during a sport competition. In this article, grounded in appraisal emotion approaches, self-regulation theory, as well as the biocultural framework of nonverbal behavior, I present findings on (a) how these affective expressive behaviors can partially be explained (i. e., their antecedents) and (b) how they might influence sport performance (i. e., their consequences). Regarding their antecedents, situational factors related to the importance of the situation, the outcome of the point, as well as players` self-talk have been shown to be associated with these behaviors. While players report various performance-related inter- and intrapersonal consequences, the findings on associations with objective performance indicators show some inconsistency. Several directions for future research are subsequently discussed that may help improve the understanding of affective expressive behaviors in sport.